2D and 3D Modeling of Rock Mechanical Properties of Khasib Formation in East Baghdad Oil Field - Steer, Hayder; Hadi, Farqad; Ellafi , Abdulaziz (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
Knowing the distribution of the mechanical rock properties and the far field stresses for the field of interest is an important task for many applications concerning reservoir geomechanics, including wellbore instability analysis, hydraulic fracturing, sand production, reservoir compaction, and subsidence. A major challenge with determining the rock's mechanical properties is that they cannot be directly measured at the borehole. Furthermore, the recovered carbonate core samples for performing measurements are limited and they provide discrete data for specific depths.   The purpose of this study is to build 2D and 3D geomechanical models of the Khasib reservoir in the East Baghdad oil field/ Central area. TECHLOG.2015.3 software was used to build the 1D-MEM while Petrel E&P 2018.2 software was used to build the 3D distributions of rock mechanical properties. The Khasib formation has nine units (from K1 to K9). The current results support the evidence that the horizontal stresses are somewhat similar for all layers in the vertical case, but their distribution varies horizontally due to the changes in pore pressures. The pore pressure increases vertically, but its distribution within one layer is different due to the production from different wells. Elastic and strength characteristics of rock, including Young modulus, Poisson ratio, and unconfined compressive strength (UCS), have the same behavior, the highest value of the parameters appeared in the surface layer (K1). This layer is more stiff than other layers that have high porosities and high permeability. The internal friction angle for all formations ranges between 38o-40o, which gives a good harmonization with the limestone friction angle. The 3D distribution of the rock's mechanical properties revealed the carbonate heterogeneity because of its marine depositional environment and complex diagenetic processes. The findings of this study can be used for future geomechanical applications in the East Baghdad oil field including wellbore stability analysis, fault reactivation, and CO2 sequestration.